Physico-chemical and antioxidant analysis of virgin coconut oil using West African tall variety - Ahmad, Zunairah (2015)
Virgin coconut oil (VCO) has been widely used traditionally in Malaysia as moisturiser and food supplement. Recently, VCO has been growing in popularity because of its better chemical and biological properties compared to coconut oil. VCO contains medium chain fatty acids of which 45- 50% lauric acid. Lauric acid has been proven to become a strong anti-inflammatory and anti-microbial agent. In the present study, the physico-chemical and antioxidant properties of VCO extracted using integrated wet process (IWP) were investigated. The physico-chemical analyses were done, which comprise fatty acid content, iodin value, free fatty acid (FFA), peroxide value, total phenolic content and antioxidant activity. The properties of fatty acid (FA) in VCO were found containing predominantly lauric acid (C12), which ranges from 50.74% to 51.12%, while the free fatty acid (FFA) content is 0.13% ± 0.06%. The FFA is an indicator of quality such as off taste and aroma. The iodin value (IV) is 12.28% ± 0.66%. Meanwhile, the peroxide value (PV) is 0.87 ± 0.02 meq oxygen/kg. The total phenolic content is about 16.02 ± 0.44 mg GAE/ 100 g oil. The antioxidant activity was determined using DPPH radical-scavenging activity and the amount of VCO extract to decrease the DPPH radical concentration by 50% is 5.07 ± 0.19 mg/L. Collectively, all results obtained in this study were found comparable with the Standard APCC except for iodin value, which has a slightly higher value compared to the standard value.